Analysis of Formative and Summative Evaluation Implementation in Physics Learning Process at MA Masyariqul Anwar - Romadon, Romadon (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
Evaluation in the learning process plays an important role in assessing students' competency achievement. Formative and summative evaluations are two main approaches in assessing the effectiveness of learning. This study aims to analyze the implementation of formative and summative evaluations in physics learning at MA Masyariqul Anwar. The research method used is a qualitative method with a case study approach. Data were collected through observation, interviews, and document analysis. The results of the study indicate that formative evaluation is implemented in the form of quizzes, discussions, and individual assignments, while summative evaluation is carried out through midterm and final exams. The obstacles faced include time constraints in implementing formative evaluation and lack of student readiness in facing summative evaluation. This study recommends increasing teacher training in formative evaluation and optimizing learning time to improve assessment quality.